Use of Eggshells as Bone Grafts around Commercially Pure Titanium Implant Screws Coated with Nano Calcium Sulfate - Dher Riyadh Kadhim; Thekra Ismael Hamad; Abdalbseet A. Fatalla (International Journal of Biomaterials)
Background. Implant insertion in regions with poor bone quantity, such as the posterior maxilla, is potentially associated with an increased rate of implant failure. Calcium sulfate can be used as the coating material for commercially pure titanium (CpTi) and as the bone graft material around implants when bound to eggshell powder to enhance the bone quality and quantity of bone defect regions. This study performed a torque removal test to evaluate the effectiveness of eggshell powder as a bone substitute for filling bone defects around CpTi-coated implants coated with nanocrystalline calcium sulfate. Materials and Methods. Eighty screw implant designs were used in the tibiae of 20 white New Zealand rabbits. A total of uncoated 20 screws constituted the control group, and the remaining 60 screws coated with nano calcium sulfate nanoparticles were used as the experimental groups as follows: 20 screws coated with nano calcium sulfate were used alone in the tibiae without gaps around them, 20 screws coated with nano calcium sulfate were used with the gaps made around them and filled with eggshell powder as the bone graft material, and 20 screws coated with nano calcium sulfate were used with the gaps made around them left unfilled. Results. After 2 to 6 weeks of healing, a significant improvement in bone regeneration and an increase in torque removal values were observed when the bone defect around the CpTi implant coated with nano calcium sulfate was filled with eggshell powder as the bone substitute. Conclusions. Nano calcium sulfate particles applied through the dip-coating method can successfully work as the coating material of CpTi implants. These particles work in synergy with eggshell powder to act as the bone graft around the implants.